The Treatment Of Skeleto-Dental Openbite Wıth Mandıbular Retrusion (Case Report) - Meliha Rübendüz (Galenos Yayinevi, 1997)
In this paper it is aimed to evaluate the results of the orthopedic treatment of an individual with skeleto-dental openbite combined with mandibular retrusion and long face syndrome in early period of the development, and orthodontic treatment for the elimination of crowding in late period of the development, and retention treatment.